An Act of Love: Three Experiences of Self-Decolonization in the Academic Community of the United Kingdom - Keren Poliah; Vashti Suwa Gbolagun; John Yuen Ka Keung; Hannah Helm; David Junior Gilbert (The February Journal)
This narrative essay presents testimonies that uncover the fragmented identity of members of minoritized ethnic groups in the academic context of the United Kingdom. It discusses outcomes of a project which, as part of an Equality, Diversity, and Inclusion (EDI) scholarship from the Doctoral School of the University of Salford, gathered testimonies and stories of international postgraduate doctoral researchers highlighting that the process of decolonization should start from within. Demonstrating how deeply coloniality pervades lands and people, these narratives unveil realities of not fitting in, performing unconventionality, and placing marginalized voices at the forefront. The authors of this essay narrate their journeys towards recognizing their commitment to decolonizing themselves, and underline how this process can provoke change in others.